Estimation of left ventricular functions in patients with subclinical hypothyroidism: a meta-analysis - Li, Binyi; Huang, Yong; Li, Zheng (Frontiers in Endocrinology, 2023)
Objective To evaluate left ventricular (LV) function in patients with subclinical hypothyroidism (ScH) compared to healthy individuals and to provide clinical hints for practitioners. Methods PubMed, Embase, Cochrane Library, and Web of Science were systematically searched in this meta-analysis. Studies evaluating LV function in ScH patients were included. Standardized mean difference (SMD) and the 95% confidence intervals (CIs) were calculated as effect size. Heterogeneity and risks of bias of included studies were assessed. Results A total of 9 studies were identified as eligible. The SMD for fractional shortening (FS, %) was -0.21 (95% CI: -0.60, 0.17; z = -1.08, p = 0.2788). The pooled SMD for systemic vascular resistance (SVR, dynes/sec·cm-5) was -0.41 (95% CI: -1.31, 0.49; z = -0.89, p = 0.3744). The pooled SMD for early diastolic mitral flow velocity/late diastolic mitral flow velocity (E/A) ratio was -0.74 (95% CI: -1.09, -0.39; z = -4.13, p < 0.001). The pooled SMD for ejection fraction (EF, %) was -0.35 (95% CI: –0.59, -0.12; z = -2.95, p = 0.0032). Conclusion ScH patients had significantly worse LV function parameters than healthy controls. These changes in LV function may be involved in the management of ScH.